LITERATURE REVIEW: Non-Indicated Use of N-Acetylcysteine against Oxidative Stress-Mediated Organophosphate Toxicity - aurelie_reginia iteh; Primayanti Nurul Ilmi; Amara Ayu Karlina; Bimo Asrul Seno; Femmita Alifa Yushanti; Haurannisa Zidny; Na’Ilah Faizah Saifani Archam; Pirda Baroqah; Tisya Mayra Arsalna Poetri; Vivian Xaviera Azzahra (Journal of Research in Pharmacy and Pharmaceutical Sciences, 2026)
Organophosphate poisoning poses a significant health threat due to its ability to induce oxidative stress, cellular damage, and neurotransmitter disruption. Pharmacovigilance plays a crucial role in monitoring and preventing adverse effects associated with medical products, including responses to toxic exposure. This study aims to evaluate the protective role of N-acetylcysteine (NAC) against organophosphate-induced toxicity through a comprehensive literature review. The method employed includes a review of eight experimental studies conducted between 2017 and 2023, involving both in vivo (animal models) and in vitro (cell cultures and human samples) approaches. The results indicate that NAC significantly reduces oxidative stress biomarkers, enhances antioxidant enzyme activity, suppresses apoptosis, and restores inhibited cholinesterase activity. Moreover, NAC improves histopathological alterations in organs exposed to organophosphates, including the liver, kidneys, brain, and testes. In conclusion, NAC demonstrates strong therapeutic potential as a standalone or adjunct agent in managing organophosphate toxicity through its antioxidant, anti-inflammatory, and cytoprotective mechanisms.